Procedural Legal Responsibility: A New Reading - Vladimir Valentinovich Kozhevnikov; Muhammad Ridwan (Polit Journal Scientific Journal of Politics, 2025)
Paying attention to various options for understanding legal liability, the position in which legal liability is interpreted as the application of measures of state coercion is recognized as more preferable. Among its features, special attention is paid to such a feature, according to which it entails negative consequences, the imposition of new additional obligations on offenders. This feature should be especially taken into account when differentiating measures of legal (criminal procedural) liability and protective measures (restorative criminal procedural measures). Procedural legal liability is considered as a complex (integrated) legal institution consisting of norms of both branches of procedural and substantive law. In turn, criminal procedural liability, using specific legal norms as an example, is analyzed as a sub-institute of procedural liability. The purpose of this study was to form the author's understanding of criminal procedural liability. The hypothesis is the statement of the fact that in most cases procedural liability is unreasonably understood as one of the types of legal liability